Prion strain discrimination based on rapid in vivo amplification and analysis by the cell panel assay. - Yervand Eduard Karapetyan; Paula Saá; Sukhvir Paul Mahal; Gian Franco Sferrazza; Alexandra Sherman; Nicole Salès; Charles Weissmann; Corinne Ida Lasmézas (PLoS ONE, 2009)
Prion strain identification has been hitherto achieved using time-consuming incubation time determinations in one or more mouse lines and elaborate neuropathological assessment. In the present work, we make a detailed study of the properties of PrP-overproducing Tga20 mice. We show that in these mice the four prion strains examined are rapidly and faithfully amplified and can subsequently be discriminated by a cell-based procedure, the Cell Panel Assay.